Fortpflanzung und Geschlecht: Zur Konstruktion und Kategorisierung der generativen Praxis - Heitzmann, Daniela (transcript, 2017)
Reproduction as the 'most natural' phenomenon in the world is often used as the reason for the gender gap and serves as justification for the hierarchically-structured relations between genders. Using the sociology of Pierre Bourdieu as a basis, Daniela Heitzmann asks how this supposedly natural fact can be understood as a social phenomenon in order to analyse its close connection to womanhood, on the one hand, and the rather loose relation to masculinity, on the other. In doing so, she develops a concept of generative practice that leads into a research programme on the genesis of presentations of generativity which particularly highlights the role of the social construction aspect of sociology.